Noah Haynes Swayne signature - Swayne, Noah Haynes, 1804-1884.
Signature of Justice Swayne.
Associate justice of the U.S. Supreme Court, state legislator from Ohio, and lawyer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: United States. -- Supreme Court; Jurists; Lawyers; Legislators -- Ohio